Oral contraception does not alter single dose saquinavir pharmacokinetics in women - Fröhlich, Margit; Burhenne, Jürgen; Martin-Facklam, Meret; Weiß, Johanna; Wolff, Michael von; Strowitzki, Thomas; Walter-Sack, Ingeborg; Haefeli, Walter E. (British journal of clinical pharmacology, 2004)
Aims Women experience more adverse drug reactions (ADR) to antiretroviral therapy than men. This may be attributed to higher plasma concentrations of protease inhibitors due to pharmacokinetic interactions with hormonal preparations. Thus, in the present study we aimed to investigate the influence of oral contraceptives (OC) on the pharmacokinetics of the protease inhibitor saquinavir. Methods Saquinavir was administered in a hard gelatin capsule formulation (Invirase®) to rule out confounding by pharmaceutical aids of the more frequently used soft gelatin capsule. After an overnight fast, eight healthy female participants ingested a single oral dose of 600 mg saquinavir immediately before and after the 19th dose of a combined, low dose OC (0.03 mg ethinylestradiol, 0.075 mg gestodene) in a prospective, fixed sequence study design. The first saquinavir application was scheduled on day 1, 2, or 3 of the individual menstrual cycle. Plasma concentrations of saquinavir and relative concentrations of its M2&M3-hydroxy metabolites were determined by LC/MS/MS for 48 h. Results Intake of OC resulted in a significant decrease in morning serum concentrations (before intake of OC, compared to day 19 of OC therapy) of 17β-estradiol by −23.4 pg ml−1 (57%, 95%CI: −76% to −37.4%); progesterone by −0.25 ng ml−1 (33%, 95%CI: −45.3% to −21.5%); follicle-stimulating hormone by −4.06 U l−1 (82%, 95%CI: −96.5% to −67.7%); and luteinizing hormone by −3.49 U l−1 (74%, 95%CI: −93 to −54.6%). Conversely, sexual hormone binding globulin serum concentrations increased by 83.6 nmol l−1 (205%, 95%CI: 32.2% to 377%). Pharmacokinetic parameters of saquinavir (AUC, Cmax, tmax, t1/2, CLR) were not affected by OC, nor was the relative metabolic ratio of saquinavir/M2&M3-hydroxy saquinavir. Furthermore, there was no association of serum hormone concentrations or MDR1-polymorphisms (C3435T and G2677T) with pharmacokinetic parameters of saquinavir. Conclusions There was no effect of OC on saquinavir pharmacokinetics. Thus, pharmacokinetic interactions of synthetic sexual steroids with saquinavir are not likely to account for the increased ADR to antiretroviral therapy seen in women.
Gesehen am 25.05.2021